CREG1 improves the capacity of the skeletal muscle response to exercise endurance via modulation of mitophagy. Issue 12 (2nd December 2021) - Song, HaiXu; Tian, Xiaoxiang; Liu, Dan; Liu, Meili; Liu, Yanxia; Liu, Jing; Mei, Zhu; Yan, Chenghui; Han, Yaling
ABSTRACT: CREG1 (cellular repressor of E1A-stimulated genes 1) is involved in tissue homeostasis and influences macroautophagy/autophagy to protect cardiovascular function. However, the physiological and pathological role of CREG1 in the skeletal muscle is not clear. Here, we established a skeletal muscle-specific creg1 knockout mouse model ( creg1;Ckm-Cre ) by crossing the Creg1 -floxed mice ( Creg1 fl/fl ) with a transgenic line expressing Cre recombinase under the muscle-specific Ckm (creatine kinase, muscle) promoter. In creg1;Ckm-Cre mice, the exercise time to exhaustion and running distance were significantly reduced compared to Creg1 fl/fl mice at the age of 9 months. In addition, the administration of recombinant (re)CREG1 protein improved the motor function of 9-month-old creg1;Ckm-Cre mice. Moreover, electron microscopy images of 9-month-old creg1;Ckm-Cre mice showed that the mitochondrial quality and quantity were abnormal and associated with increased levels of PINK1 (PTEN induced putative kinase 1) and PRKN/PARKIN (parkin RBR E3 ubiquitin protein ligase) but reduced levels of the mitochondrial proteins PTGS2/COX2, COX4I1/COX4, and TOMM20. These results suggested that CREG1 deficiency accelerated the induction of mitophagy in the skeletal muscle. Mechanistically, gain-and loss-of-function mutations of Creg1 altered mitochondrial morphology and function, impairing mitophagy in C2C12 cells. Furthermore, HSPD1/HSP60 (heat shock protein 1) (401–573 aa) interacted with CREG1 (130–220 aa) to antagonize the degradation of CREG1 and was involved in the regulation of mitophagy. This was the first time to demonstrate that CREG1 localized to the mitochondria and played an important role in mitophagy modulation that determined skeletal muscle wasting during the growth process or disease conditions. Abbreviations : CCCP: carbonyl cyanide m-chlorophenylhydrazone; CKM: creatine kinase, muscle; COX4I1/COX4: cytochrome c oxidase subunit 4I1; CREG1: cellular repressor of E1A-stimulated genes 1; DMEM: dulbecco's modiﬁed eagle medium; DNM1L/DRP1: dynamin 1-like; FCCP: carbonyl cyanide p-triﬂuoro-methoxy phenyl-hydrazone; HSPD1/HSP60: heat shock protein 1 (chaperonin); IP: immunoprecipitation; MAP1LC3B/LC3B: microtubule-associated protein 1 light chain 3 beta; MFF: mitochondrial fission factor; MFN2: mitofusin 2; MYH1/MHC-I: myosin, heavy polypeptide 1, skeletal muscle, adult; OCR: oxygen consumption rate; OPA1: OPA1, mitochondrial dynamin like GTPase; PINK1: PTEN induced putative kinase 1; PPARGC1A/PGC-1α: peroxisome proliferative activated receptor, gamma, coactivator 1 alpha; PRKN/PARKIN: parkin RBR E3 ubiquitin protein ligase; PTGS2/COX2: prostaglandin-endoperoxide synthase 2; RFP: red fluorescent protein; RT-qPCR: real-time quantitative PCR; SQSTM1/p62: sequestosome 1; TFAM: transcription factor A, mitochondrial; TOMM20: translocase of outer mitochondrial membrane 20; VDAC: voltage-dependent anion channel.